Evaluation of functional family therapy in an Irish context. Issue 1 (3rd December 2013) - Graham, Clare; Carr, Alan; Rooney, Brendan; Sexton, Tom; Wilson Satterfield, Laura Rachel
<x xml:space="preserve">Abstract</x> In an Irish context we conducted a retrospective archival study of functional family therapy (FFT) for adolescents with behavioural problems. Strengths and difficulties questionnaire data were collected from 118 families at the beginning and end of therapy (at baseline and follow up for dropouts) in a community‐based clinic in a socially disadvantaged Dublin suburb. Analyses of the improvement in mean scores and clinical recovery rates showed that the outcome was associated with treatment completion and the extent to which therapists adhered to the FFT treatment manual. Therapy completers treated by high‐adherent therapists had the most favourable outcome. In contrast, the worst outcome occurred for dropouts. The outcome of cases treated by low‐adherent therapists fell between these two extremes. These results show that FFT may be effectively implemented in an Irish context, and that the effectiveness of treatment is associated with families remaining in treatment for an average of seventeen sessions, and receiving treatment from therapists who implement FFT with a high degree of fidelity. Practitioner points Use functional family therapy to treat adolescents with behavioural problems. To maximize benefits to clients, adhere to the functional family therapy treatment protocol when conducting therapy.